Providing pharmacy services during the coronavirus pandemic - Liu, Shao (Int J Clin Pharm, 2020)
The coronavirus disease 19 (COVID-19) is quickly spreading across China and globally. Pharmacy services are an important pillar in public health to prevent and contain the COVID-19 pandemic. Chinese pharmacists have acted swiftly in the public health response in China, such as drafting professional service guidance to pharmacists and pharmacies, establishing emergency drug formularies, monitoring and resolving drug shortages, establishing remote pharmacy services to prevent human-to-human infections, providing event-driven pharmaceutical care, educating the public on infection prevention and disease management, and participating in clinical trials and drug evaluation. This commentary reviews the unique needs of pharmacy services in the COVID-19 pandemic, and shares our experiences with the international pharmacy community in the response to these needs.